Pinah Laman: The Construction of Religious and Ethnic Identity Within the Mentuka Dayak of West Kalimantan - Felisitas Yuswanto; Sekar Ayu Aryani; Ahmad Muttaqin (Al-Albab, 2022)
For the Mentuka Dayak tribe, Pinah Laman is a change in ethnic and religious identity. Pinah Laman in the Mentuka Dayak community is perceived as a cultural space for community members who convert to a particular religion. Generally, religious conversion occurs in this society from Catholicism to Islam. The new identity is given by the term ‘Sinan.’ But on the other hand, the Sinan identity has its own meaning. Sinan is a new identity given to those who have converted to another religion. Because of this Pinah Laman custom, they do not get their tribal rights, such as: performing the Mentuka Dayak traditional ceremonies. This article aims to explore the construction of a new identity from the construction process of religious identity, which involves custom. In addition, this article also explains the form of religious identity construction that occurs among the Mentuka Dayak tribe and the new converts who experience it. Religious conversion is inseparable from the driving factors for the emergence of a new identity and the implications of constructing a new identity due to the conversion process. This article was compiled from the results of research using the ethnographic method. The results of this research show that Pinah Laman is a conversion process of a Christian or Catholic Dayak to Islam. This impacts the social sanctions one receives from one’s social group. For the Mentuka Dayak people, when someone decides to change his religion, he must be willing to give up his Dayak ethnicity. One of the social effects felt by a new convert in the Dayak tribe is that he will be given a nickname or term ‘Sinan.’ Based on the results of this research, the term Sinan has a negative connotation. This is because those who change their religion are ultimately not given the freedom to practice Dayak customs as usual.